Osmotic dehydration of pineapple (Ananas comosus L. Merr.) using sucrose-sorbitol mixtures and microbial stability during storage - Lim, Chee Hui (2017)
Osmotic dehydration (OD) is an effective preservation technique to remove water from fruits and produce high quality products with minimal nutrients loss. Sorbitol is a low-glycemic carbohydrate with complementary sugar’s functionality with lower glycemic index compared to sucrose. The osmotic dehydration kinetic and microbial stability of the osmodehydrated pineapple of sorbitol-sucrose mixtures during storage were determined in this study. OD were conducted using 65 °Brix sucrosesorbitol mixture ranging from 0 to 100 % concentration at 40 °C for 240 minutes and subjected to hot air drying at 50 °C to approximately 30 % moisture content. Samples were vacuum-packed and stored at 4 °C for storage study. Textural, moisture content, aw, pH, colour, flavonoids, vitamin C and bromelain were determined using texture analyzer, moisture analyzer, water activity meter, pH meter, Hunter LAB calorimeter, spectrophotometer, standard Vitamin C AOAC 967.21 and casein digestion unit (CDU) method, respectively. The results showed that in general all formulations studied gave decreasing trend for weight reduction (WR) and water loss (WL) and increasing trend for solutes gain (SG). Sorbitol substitution at 75 % and 100 % were recommended for osmodehydrated pineapple because both formulations gave the lowest WR, highest WL and SG values, which fulfilled the requirement as a high quality osmodehydrated fruits. In addition, both formulations had the lowest water activity, low pH values, medium firmness and no obvious browning. Results on microbial stability showed that osmodehydrated pineapple with sorbitol can be stored at 4ºC for more than 2 months at bacteria count < 106 CFU/g and yeast and mould ≤ 104 CFU/g. However, there were no significant effects of different osmotic solutions used on the retention of vitamin C content and total flavonoid content because all showed degradation throughout storage and firmness of osmodehydrated pineapple decreased with storage. However, for bromelain activity, sorbitol treated pineapple is significant in retaining the bromelain activity. In conclusion, sorbitol treated osmodehydrated pineapple have a better extended shelf life and better retention of bromelain activity which showed that sorbitol can be used as an alternative osmotic solution in osmotic dehydration of pineapple.